THE RELATIONSHIP BETWEEN FAMILY EMPOWERMENT AND FAMILY INDEPENDENT IN CARING PATIENTS WITH LUNG TUBERCULOSIS IN BANJAR REGENCY, INDONESIA - M Noor Ifansyah; Tintin Sukartini; A Aziz Alimul Hidayat (Alta Dharma Publisher, 2019)
Tuberculosis is a direct contagious disease caused by pulmonary tuberculosis germs (Mycobacterium Tuberculosis), which is one of the top 10 conditions that cause death in the world. This study aims to identify the relationship between family empowerment and family independence in caring for patients with lung tuberculosis in Banjar Regency. The cross-sectional study design was applied in this study. We recruited 120 families with pulmonary tuberculosis patients using a simple random sampling. The results showed that there is a correlation between family empowerment and family independent in caring for patients with lung tuberculosis with p-value: 0.001 < 0.05. Empowerment of the family can help the family in carrying out its role in caring for clients of pulmonary tuberculosis independently. Keywords: Empowerment, Independence, Family, pulmonary tuberculosis